Physiological development of junior windsurfers to prepare for the change of Olympic race class from RS:X to iQFoil - Chan, Y. Y.; Tai, C. H. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In November 2019, the World Sailing Council has approved Starboard iQFoil to replace RS:X as the windsurfing equipment for Olympic Games from Paris 2024 [1]. After this decision was made, competitive windsurfing around the world has gradually transit their program to iQFoil focus, with the first iQFoil Senior and Youth World Championships being held in 2021. One of the main differences between iQFoil and RS:X is that iQFoil have foil instead of fin under the board which allow a faster speed in the same wind conditions [2]. Coaches and athletes have therefore applied different training strategies to adopt the changes. The aim of this study was to investigate the difference in physiological development for junior windsurfers in preparing to race in iQFoil class when comparing with the RS:X class.